Marriage within The Same Clan (Nikah Samih): An Analysis of Alas Customary Law from the Perspective of Islamic Law - Mhd. Haikal; Milhan (Nizham Jurnal Studi Keislaman, 2026)
This study examines the prohibition of intra-clan marriage (Nikah Samih) in Alas customary law and analyzes the practice through Islamic law and maqāṣid al-sharīʿah. The study aims to clarify the practice, its normative foundations, and its relevance to Islamic legal principles within the Alas community. A qualitative empirical design with an ethnographic approach guided the research; data were collected through literature review, in-depth interviews with customary and religious leaders, and field observation in Southeast Aceh Regency. Findings indicate that Alas customary law treats same-clan marriage as equivalent to consanguineous marriage, imposes strict prohibition, and applies customary sanctions as social control to protect family honour. The prohibition does not correspond to religiously forbidden (mahram) categories as listed in the Qur’an (An-Nisāʼ: 22–24). The community regards Nikah Samih as local wisdom that may be observed provided it does not conflict with sharīʿah. A maqāṣid analysis demonstrates alignment of the customary prohibition with objectives of protecting lineage, life, intellect, and social harmony. The study concludes that Nikah Samih operates as a contextual customary norm motivated by maṣlaḥah (public interest) rather than as an absolute sharīʿah rule.